OVERVIEW OF PSYCHOLOGICAL WELL-BEING AND FORGIVENESS OF CHRISTIAN YOUTH IN NORTH SUMATERA - Pamela Hendra Heng; Desiree Gracia Nelwan; Septi Lathiifah (MAHABBAH: Journal of Religion and Education, 2021)
The entire world is being attacked by a pandemic outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) or what we know as COVID-19. The Indonesian government policy of limiting the crowd of people when socializing affects various activities of young people at church, including in North Sumatera. This causes the psychological well-being (PWB) of the youth to be disturbed. Research shows Christian youths carry out activities such as wasting time on social media and online games that may lead to gambling (Jap et al., 2013) while neglecting their education, which is contrary to Christian teachings. Constantly pressured for neglecting responsibility and doing sins may affect PWB in youth, and forgiveness from God, their family and themselves may help increase PWB. Pre and post-test of PWB and forgiveness are administered. The instrument used is the PWB questionnaire based on Ryff's (1995) theory and TRIM-18 based on McCullough and Hoyt (2002). The subjects are adolescents and young adults aged 11-40 years in North Sumatera. Results show that both variables are high. There were differences based on participants’ educational background and whether or not the participants read the bible everyday in the PWB post-test data. As for the forgiveness, results show that there were differences based on educational background and occupation in the pre-test data, while in the post-test data, there is a difference based on how many times an individual reads the bible in a day.